Glass formation of a DMSO – water mixture probed with a photosynthetic pigment - Huerta-Viga, Adriana (2020)
Despite their extensive industrial usage, glass-forming liquids are not fully understood, and methods to investigate their dynamical heterogeneity are sought after. Here we show how the appearance of a second component in the visible absorption spectrum of a photosynthetic pigment upon cooling can be used to probe the glass transition of a dimethylsulfoxide–water mixture. The changes in the relative ratio of the two components with respect to temperature follow a sigmoid curve, and we show that the second component arises due to protonation of the pigment at low temperatures. Furthermore, from visible transient absorption spectra we show that, unlike the first component, the dynamics of the second component slows down significantly at lower temperatures, suggesting that there are two distinct environments with fast and slow fluctuations. Our results therefore enable a new method to characterize the dynamical heterogeneity of glass-forming liquids.